Using comprehensive two-dimensional gas chromatography retention indices to estimate environmental partitioning properties for a complete set of diesel fuel hydrocarbons - Arey, J. S.; Nelson, R. K.; Xu, L.; Reddy, C. M. (Analytical Chemistry, 2005)
Comprehensive two-dimensional gas chromatography (GC x GC) provides nearly complete composition data for some complex mixtures such as petroleum hydrocarbons. However, the potential wealth of physical property information contained in the corresponding two-dimensional chromatograms is largely untapped. We developed a simple but robust method to estimate GC x GC retention indices for diesel-range hydrocarbons. By exploiting n-alkanes as reference solutes in both dimensions, calculated retention indices were insensitive to uncertainty in the enthalpy of gas-stationary-phase transfer for a suite of representative diesel components. We used the resulting two-dimensional retention indices to estimate the liquid vapor pressures, aqueous solubilities, air-water partition coefficients, octanol-water partition coefficients, and vaporization enthalpies of a nearly complete set of diesel fuel hydrocarbons. Partitioning properties were typically estimated within a factor of 2; this is not as accurate as some previous estimation or measurement methods. However, these relationships may allow powerful and incisive analysis of phase-transfer processes affecting petroleum hydrocarbon mixtures in the environment. For example, GC x GC retention data might be used to quantitatively deconvolve the effects of water washing and evaporation on environmentally released diesel fuels.
id: 1700; 985UM Times Cited:30 Cited References Count:56